Whether the Bankruptcy Receiver is a Procedural Substitute? - Kolarov, Todor (Yearbook of the Law Department, 2021)
The article discourses whether the bankruptcy receiver is a procedural substitute. Upon discussing different scholarly opinions, the supported opinion is that the receiver does not have the characteristics of a procedural substitute of the creditors or the debtor.